Arsenic and Heavy Metals in Vietnamese Rice: Assessment of Human Exposure to These Elements through Rice Consumption - Dinh Binh Chu; Hung Tuan Duong; Minh Thi Nguyet Luu; Hong-An Vu-Thi; Bich-Thuy Ly; Vu Duc Loi (Journal of Analytical Methods in Chemistry)
In this work, twelve heavy metals and arsenic, As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, and Zn, in a rice sample collected from some areas of Vietnam have been quantified and implemented by using multiple analytical platforms such as ICP-MS, AAS, and mercury analyser. Seventy rice samples collected from the Red River Delta and mining zone activity were analysed. Concentration of heavy metals and arsenic in rice was analysed after appropriated sample digestion using internal or external calibration curves. The mean concentration (mg kg−1 dried weight) of the analysed elements in rice samples decreased on the order of Mn (19.268) > Fe (13.624) > Zn (8.163) > Cu (3.138) > Ni (0.384) > Cr (0.296) > Co (0.279) > As (0.115) > Cd (0.111) > Pb (0.075) > Hg (0.007) > Se (<LOD). Mercury, a highly toxic element, has been only found in rice samples collected in the mining activity zone (frequency detection 14.5% of total samples). The experimental results indicated that the heavy metals and arsenic found in rice collected from mining activity zone were higher than those in rice harvested from normal cultivated areas like the Red River Delta. The heavy metals and arsenic content in Vietnamese rice samples were also compared with the concentration of heavy metals in other foreign rice samples in some recent publications. The estimated daily intake through rice consumption was calculated and compared with the level proposed by the Food and Agriculture Organization of the United Nations. The results indicated that the provisional daily intake of Cd was higher than the level proposed by FAO, while the intake of other heavy metals was in an acceptable range of CODEX standard.